Solid electrolyte and method for producing solid electrolyte

By adding boron to the 3LiOH·Li2SO4 solid electrolyte and adopting specific manufacturing processes, the problem of reducing lithium ion conductivity at high temperatures is solved, and the lithium ion conductivity is maintained in the range of room temperature to high temperatures is achieved, and it is suitable for lithium ion secondary Batteries and capacitors.

CN113597698BActive Publication Date: 2025-01-03NAGOYA INSTITUTE OF TECHNOLOGY +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN201980093401.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2019-03-26
Filing Date
2019-10-24
Publication Date
2025-01-03
Estimated Expiration
2039-10-24

AI Technical Summary

Technical Problem

The existing Li2SO4-LiOH solid electrolytes are prone to decrease in lithium ion conductivity at high temperatures, and cannot maintain sufficient lithium ion conductivity from room temperature to high temperature range.

Method used

By adding boron to the 3LiOH·Li2SO4 solid electrolyte, a solid electrolyte containing boron is formed, and its crystal structure is identified by X-ray diffraction. A solid electrolyte with improved lithium ion conductivity maintenance is produced by combining mechanical ball milling and melting processes.

Benefits of technology

After maintaining high temperature for a long time, the reduction of lithium ion conductivity is significantly suppressed, and the maintenance of lithium ion conductivity is improved. It is suitable for power storage components such as lithium ion secondary batteries and capacitors.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0003238700930000081
    Figure BDA0003238700930000081
Patent Text Reader

Abstract

The present invention provides a 3LiOH·Li 2 SO 4 The solid electrolyte was identified as 3LiOH·Li by X-ray diffraction. 2 SO 4 , and also contains boron.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a solid electrolyte and a method for producing the solid electrolyte. Background Art

[0002] In recent years, research and development of solid electrolytes used in storage elements such as lithium-ion secondary batteries and capacitors has been actively carried out. In particular, it is desired to develop a solid electrolyte that can maintain sufficient lithium ion conductivity from room temperature to high temperature. Here, the following scheme is proposed in Non-Patent Document 1, that is, Li 2 SO 4 After homogeneously melting LiOH, the solidified body is obtained by quenching, and the solidified body is used as a solid electrolyte. In particular, the solid electrolyte can be used for devices operating at low temperatures.

[0003] Prior art literature

[0004] Non-patent literature

[0005] Non-patent literature 1: VKDESHPANDE, FCRAGHUWANSHI AND K.SINGH, “ELECTRICAL CONDUCTIVITY OF THE 2 SO 4 -LiOH SYSTEM", Solid State Ionics 18&19(1986)378-381 Summary of the invention

[0006] However, it cannot be said that the lithium ion conductivity of the solid electrolyte described in Non-Patent Document 1 is sufficiently high at room temperature. In addition, the temperature dependence of the conductivity of the solid electrolyte in Non-Patent Document 1 is low, and the conductivity increase effect brought about by the temperature increase cannot be expected. In other words, the solid electrolyte cannot be said to be a material with sufficient lithium ion conductivity from room temperature to high temperature. In view of these problems, the inventors of the present invention have obtained the following insights, namely, 3LiOH·Li 2 SO 4 The solid electrolyte shown exhibits high lithium ion conductivity at 25° C. However, it is known that there is another problem that the lithium ion conductivity is likely to decrease when the material of the above composition is kept at high temperature for a long time.

[0007] The inventors of the present invention have recently obtained the knowledge that by using a substance identified as 3LiOH·Li 2 SO 4 The solid electrolyte further contains boron, which can significantly suppress the decrease in lithium ion conductivity even after being kept at a high temperature for a long time.

[0008] Therefore, an object of the present invention is to provide 3LiOH·Li which can significantly suppress the decrease in lithium ion conductivity even after being kept at high temperature for a long time. 2 SO 4 Based solid electrolyte.

[0009] According to one embodiment of the present invention, a solid electrolyte is provided, which is identified as 3LiOH·Li by X-ray diffraction. 2 SO 4 A solid electrolyte further comprising boron.

[0010] According to another embodiment of the present invention, a method for manufacturing a solid electrolyte is provided, which is the method for manufacturing the solid electrolyte described above, wherein the method comprises: 2 SO 4 Li 3 BO 3 The process of melting the raw materials and cooling them to form a solid.

[0011] According to another embodiment of the present invention, a method for manufacturing a solid electrolyte is provided, which is the method for manufacturing the solid electrolyte described above, wherein the method comprises: 2 SO 4 Li 3 BO 3 The powder is mixed and crushed by mechanical ball milling to synthesize solid electrolyte powder. DETAILED DESCRIPTION

[0012] Solid electrolyte

[0013] The solid electrolyte of the present invention is identified as 3LiOH·Li by X-ray diffraction. 2 SO 4 The solid electrolyte is identified as 3LiOH·Li 2 SO 4 The solid electrolyte further contains boron, which can significantly suppress the decrease in lithium ion conductivity even after being kept at high temperature for a long time. That is, as described above, the inventors of the present invention have obtained the following findings, namely, 3LiOH·Li 2 SO 4 The solid electrolyte shown in FIG. 1 exhibits high lithium ion conductivity at 25°C. However, it is known that there is another problem, that is, when the above composition is kept at high temperature for a long time, the lithium ion conductivity is easily reduced. In this regard, by making the 3LiOH·Li 2 SO 4The solid electrolyte further contains boron, which can solve the above problems. The mechanism by which the ion conductivity maintenance rate can be improved by containing boron is still uncertain. According to X-ray diffraction measurement, by containing boron, 3LiOH·Li 2 SO 4 The diffraction peak of 3LiOH·Li is slightly shifted to the high angle side. From this point, it is inferred that boron enters 3LiOH·Li 2 SO 4 Any site in the crystal structure, so that the stability of the crystal structure with respect to temperature is improved.

[0014] Therefore, the solid electrolyte of the present invention is preferably used for storage elements such as lithium ion secondary batteries and capacitors, and is particularly preferably used for lithium ion secondary batteries. The lithium ion secondary battery can be an all-solid battery (for example, an all-solid lithium ion secondary battery). In addition, the lithium ion secondary battery can be a liquid battery (for example, a lithium-air battery) using a solid electrolyte as a separator and having an electrolyte between the separator and the opposing electrode.

[0015] As described above, the solid electrolyte of the present invention is 3LiOH·Li 2 SO 4 That is, the solid electrolyte contains 3LiOH·Li 2 SO 4 As the main phase. 2 SO 4 , can be confirmed by identifying it in the X-ray diffraction pattern using 032-0598 in the ICDD database. Here, “3LiOH·Li 2 SO 4 " means: the crystal structure is regarded as 3LiOH·Li 2 SO 4 The same substance does not need to have the same crystal composition as 3LiOH·Li 2 SO 4 That is, it has the same 2 SO 4 The same crystal structure is sufficient, and the composition deviates from LiOH:Li 2 SO 4 =3:1 is also included in the solid electrolyte of the present invention. Therefore, even a solid electrolyte containing boron (for example, 3LiOH·Li in which the X-ray diffraction peak is shifted to the high angle side due to the solid solution of boron) 2 SO 4 ), as long as the crystal structure is regarded as 3LiOH·Li 2 SO 4 The same, that is, 3LiOH·Li 2 SO4 Likewise, the solid electrolyte of the present invention is also allowed to contain inevitable impurities.

[0016] Therefore, in addition to 3LiOH·Li 2 SO 4 In addition, a heterogeneous phase may be included. The heterogeneous phase may include a plurality of elements selected from Li, O, H, S and B, or may be composed only of a plurality of elements selected from Li, O, H, S and B. Examples of heterogeneous phases include LiOH, Li 2 SO 4 and / or Li 3 BO 3 For these heterogeneous phases, it is believed that 3LiOH·Li 2 SO 4 The substance left over from the unreacted raw materials. However, since it does not help conduct lithium ions, except for Li 3 BO 3 However, considering that it can help improve the lithium ion conductivity maintenance rate after high temperature and long-term maintenance, it can contain Li in a desired amount. 3 BO 3 However, the solid electrolyte may also be composed of 3LiOH·Li 2 SO 4 Single-phase composition.

[0017] The solid electrolyte of the present invention also contains boron. The molar ratio (B / S) of boron B contained in the solid electrolyte to sulfur S is preferably greater than 0.002 and less than 1.0, more preferably greater than 0.003 and less than 0.9, and further preferably greater than 0.005 and less than 0.8. If the boron content is a small amount, the maintenance rate of lithium ion conductivity at high temperature is reduced, but if the B / S is within the above range, the maintenance rate of lithium ion conductivity can be improved. In addition, if the boron content is high, it is possible to cause the absolute value of lithium ion conductivity to decrease, but if the B / S is within the above range, the content of unreacted heterogeneous phases containing boron is reduced, and therefore, the absolute value of lithium ion conductivity can be increased.

[0018] The solid electrolyte of the present invention is identified as 3LiOH·Li in the X-ray diffraction pattern using CuKα as the radiation source. 2 SO 4The half-value width of the peak near 2θ=18.4° is preferably 0.500° or less, more preferably 0.400° or less, and further preferably 0.200° or less. If it is in such a range, the lithium ion conductivity maintenance rate after high temperature and long-term maintenance can be further improved. The smaller the half-value width, the higher the crystallinity, so it is preferred that the lower limit is not particularly limited, and is typically 0.08° or more, and more typically 0.1° or more.

[0019] The solid electrolyte of the present invention is identified as a peak intensity I near 2θ=20.5° of LiOH in an X-ray diffraction pattern using CuKα as a radiation source. LiOH Compared with 3LiOH·Li 2 SO 4 The peak intensity I near 2θ=18.4° LHS The ratio of I LiOH / I LHS It is preferably less than 0.234, more preferably 0.230 or less, and further preferably 0.200 or less. If LiOH is high, the absolute value of lithium ion conductivity may decrease, but if it is within the above range, the content of LiOH decreases, so the absolute value of lithium ion conductivity can be increased.

[0020] The solid electrolyte of the present invention is identified as Li in the X-ray diffraction pattern using CuKα as the radiation source. 2 SO 4 The peak intensity I near 2θ=22.2° Li2SO4 Compared with 3LiOH·Li 2 SO 4 The peak intensity I near 2θ=18.4° LHS The ratio of I Li2SO4 / I LHS It is preferably less than 1.10, more preferably 0.50 or less, and even more preferably 0.20 or less. 2 SO 4 If the lithium ion conductivity is greater than 1%, the absolute value of the lithium ion conductivity may decrease. However, if the lithium ion conductivity is within the above range, the lithium 2 SO 4 The content rate of is reduced, so the absolute value of lithium ion conductivity can be increased.

[0021] The solid electrolyte of the present invention may be a powder compact, and is preferably a melt-solidified body (ie, a substance obtained by heating, melting, and then solidifying).

[0022] Manufacturing method

[0023] According to a preferred embodiment of the present invention, the solid electrolyte of the present invention can be manufactured by the following steps: 2 SO 4 Li 3 BO 3 The raw material is melted and cooled to form a solid. From the viewpoint of ion conductivity, the raw material used at this time preferably has a composition consisting of xLiOH·Li 2 SO 4 ·yLi 3 BO 3 The composition represented by (wherein, 2.0≤x≤4, 0.002≤y≤1) is not limited to this as long as the desired characteristics are obtained (for example, 1.0≤x≤4 may be used). For example, the solid electrolyte can be manufactured as follows, that is, (a) by 2 SO 4 Li 3 BO 3 (a) cooling the melt of the raw material (preferably the raw material of the above composition) to form a solidified body; (b) crushing or mechanically milling the solidified body to form a solid electrolyte powder; (c) forming the solid electrolyte powder by molding the solid electrolyte powder or melting the solid electrolyte powder again and then cooling and solidifying it. The cooling of the melt in (a) above can be any of quenching or annealing (for example, furnace cooling). For the mechanical ball milling in (b) above, zirconia balls and other balls and a solidified body of the solid electrolyte can be placed in a zirconia container or the like and crushed according to known methods and conditions, thereby performing mechanical ball milling. The molding in the step (c) above can be performed by various methods such as pressing (for example, metal mold pressing, cold isostatic pressing), preferably metal mold pressing. The cooling rate when the solid electrolyte powder in the step (c) is cooled after remelting is preferably 10 to 1000°C / h, and more preferably 10 to 100°C / h.

[0024] According to another preferred embodiment of the present invention, the following steps can be used to prepare the present invention, that is, 2 SO 4 Li 3 BO 3 The powders are mixed and crushed by mechanical ball milling to synthesize solid electrolyte powder. From the viewpoint of ion conductivity, the powder used at this time is preferably a powder having a composition of xLiOH·Li 2 SO 4 ·yLi 3 BO 3 The raw material composition ratio represented by (wherein 2.0≤x≤4, 0.002≤y≤1) includes LiOH powder, Li 2 SO 4 Powder and Li 3BO 3 The powder is not limited to this as long as the desired properties are obtained (for example, 1.0≤x≤4). For example, the solid electrolyte can be manufactured as follows, that is, (a) LiOH powder, Li 2 SO 4 Powder and Li 3 BO 3 The powder (preferably in the above-mentioned composition ratio) is mixed and crushed by mechanical ball milling to synthesize solid electrolyte powder; (b) the solid electrolyte powder is formed by molding or heating and melting the solid electrolyte powder and then cooling it to form a solid electrolyte. For the mechanical ball milling in the above (a), zirconia balls and other balls, LiOH powder, LiO2 and other particles can be placed in a container such as a zirconia container according to known methods and conditions. 2 SO 4 Powder and Li 3 BO 3 The powders are mixed and crushed, thereby mechanically ball milled. Through this mixed and crushed, a synthesis reaction of solid electrolyte powder can be carried out. The molding in the above-mentioned step (b) can be carried out by various methods such as pressing (for example, metal mold pressing, cold isostatic pressing), preferably metal mold pressing. The cooling rate of the solid electrolyte powder after melting in the above-mentioned step (b) is preferably 10 to 1000°C / h, more preferably 10 to 100°C / h.

[0025] Example

[0026] The present invention will be further specifically described by the following examples.

[0027] Examples 1 to 3

[0028] (1) Preparation of raw material powder

[0029] Li 2 SO 4 powder (commercially available, purity 99% or more), LiOH powder (commercially available, purity 98% or more), and Li 3 BO 3 (commercial products, purity 99% or more) were mixed at the molar ratio shown in Table 1 to obtain a raw material mixed powder. These powders were handled in an Ar atmosphere with a dew point of -50°C or less in a glove box, and sufficient care was taken to prevent moisture absorption and other changes in quality.

[0030] (2) (Mechanical ball milling)

[0031] In a glove box under Ar atmosphere, the raw material mixed powder and 10 zirconia balls (diameter 10 mm) were placed in a 45 ml zirconia pot, and the zirconia pot was completely sealed. The zirconia pot was installed in a planetary ball mill and mechanically milled at a speed of 400 rpm for 50 hours to synthesize a solid electrolyte powder.

[0032] (3) Metal mold pressing

[0033] The obtained solid electrolyte powder was pressed into a metal mold at a pressure of 750 MPa to form a granular solid electrolyte having a diameter of 10 mm and a thickness of 0.5 mm.

[0034] (4) Evaluation

[0035] The obtained solid electrolyte was evaluated as follows.

[0036] <X-ray diffraction>

[0037] The solid electrolyte was analyzed using an X-ray diffraction device (XRD, X-ray source: CuKα ray) to obtain an X-ray diffraction pattern. It should be noted that metal Si powder was added as an internal standard to align the 2θ position. The obtained X-ray diffraction pattern was compared with 032-0598 in the ICDD database to perform 3LiOH·Li 2 SO 4 Identification of crystal phase to determine the presence of 3LiOH·Li 2 SO 4 In addition, based on the XRD pattern obtained above, the 3LiOH·Li 2 SO 4 The half value width of the peak near 2θ=18.4° was calculated. Furthermore, the peak intensity I near 2θ=20.5°, which was identified as LiOH, was calculated. LiOH Compared with 3LiOH·Li 2 SO 4 The peak intensity I near 2θ=18.4° LHS The ratio (I LiOH / I LHS ). Similarly, the Li 2 SO 4 The peak intensity I near 2θ=22.2° Li2SO4 Compared with 3LiOH·Li 2 SO 4 The peak intensity I near 2θ=18.4° LHS The ratio (I Li2SO4 / I LHS ). The results are shown in Table 1.

[0038] <Ionic conductivity and conductivity retention after 100 hours at 150°C>

[0039] The lithium ion conductivity of the solid electrolyte is measured by conventional AC impedance measurement as follows. First, in an Ar atmosphere, the solid electrolyte is clamped between two stainless steel (SUS) electrodes and placed in a battery (manufactured by Hohsen Co., Ltd., button battery CR2032) for sealing to make a battery for ion conductivity measurement. The battery for ion conductivity measurement is placed in a constant temperature dryer at 150°C, and the conductivity (1 / r) is measured using an AC impedance measurement device (manufactured by BioLogic, VMP3) using the AC impedance method. Based on the measured value and the formula of lithium ion conductivity σ = L / r (1 / A), the initial lithium ion conductivity C is calculated. 0 .

[0040] In addition, after the solid electrolyte was kept at 150° C. for 100 hours in the above-mentioned battery for measuring ion conductivity, the lithium ion conductivity C was measured in the same manner as above. 1 Lithium ion conductivity C of the solid electrolyte after being kept at 150°C for 100 hours 1 Divided by the initial lithium ion conductivity C 0 The result was multiplied by 100 to determine the conductivity retention rate (%) after being kept at 150° C. for 100 hours.

[0041] <Chemical Analysis>

[0042] The solid electrolyte obtained in each example was subjected to quantitative analysis of boron and sulfur. Boron and sulfur were quantitatively analyzed by ICP atomic emission spectrometry (ICP-AES) using the calibration curve method. Each analysis value of boron and sulfur was converted into moles and calculated as B / S.

[0043] Examples 4 to 20

[0044] (1) Preparation of raw material powder

[0045] Li 2 SO 4 powder (commercially available, purity 99% or more), LiOH powder (commercially available, purity 98% or more), and Li 3 BO 3 (commercial products, purity 99% or more) were mixed at the molar ratio shown in Table 1 to obtain a raw material mixed powder. These powders were handled in an Ar atmosphere with a dew point of -50°C or less in a glove box, and sufficient care was taken to prevent moisture absorption and other changes in quality.

[0046] (2) Melt synthesis

[0047] The raw material mixed powder was placed in a crucible made of high-purity alumina in an Ar atmosphere, and the crucible was placed in an electric furnace and heat treated at 430° C. for 2 hours to produce a melt. The melt was then cooled at 100° C. / h in the electric furnace to form a solid.

[0048] (3) Mortar grinding

[0049] The obtained solidified product was pulverized in an Ar atmosphere using a mortar to obtain a solid electrolyte powder having an average particle size D50 of 5 to 50 μm.

[0050] (4) Melting

[0051] In a glove box in an Ar atmosphere, the solid electrolyte powder was pressed into a metal mold at a pressure of 250 MPa to form a granular solid electrolyte with a diameter of 10 mm. The granular solid electrolyte was sandwiched between two stainless steel (SUS) electrodes with a diameter of 10 mm and a thickness of 0.5 mm, and a 15 g weight was placed on the obtained stack, and heated at 400 ° C for 45 minutes to melt the solid electrolyte. Then, the melt was cooled at 100 ° C / h to form a solidified body.

[0052] (5) Evaluation

[0053] The obtained solidified body (solid electrolyte) was evaluated in the same manner as in Example 1. The results are shown in Table 1.

[0054] result

[0055] The preparation conditions and evaluation results of the solid electrolytes of Examples 1 to 20 are summarized in Table 1. In Examples 1 to 20, the solid electrolytes containing LiOH and Li 2 SO 4 Li 3 BO 3 In the process of synthesizing the solid electrolyte by melting or mechanically milling the raw material mixed powder and in the process of melting the solid electrolyte powder again, the weight loss is very small, as low as less than 1%. It is speculated that the composition of Li, O, H, S and B constituting the solid electrolyte has hardly changed compared with the composition at the time of mixing.

[0056] [Table 1]

[0057]

[0058] The results of Table 1 are described in detail. The main phases of the X-ray diffraction patterns of Examples 1 to 20 are consistent with 032-0598 in the ICDD database, which indicates the presence of 3LiOH·Li 2 SO 4 The main phase referred to here refers to:2 SO 4 Li 3 BO 3 It should be noted that, especially in the case of high concentration of boron, 3LiOH·Li 2 SO 4 The high-angle shift of the X-ray diffraction pattern of the crystalline phase. For example, without the addition of Li 3 BO 3 3LiOH·Li in Example 8 2 SO 4 The peak at 2θ = 18.43° is 3 BO 3 In Example 5, the peak is 18.46°. The peak moves toward the high angle side, which indicates that boron is dissolved in 3LiOH·Li 2 SO 4 In addition to the high-angle shift, it is consistent with 032-0598 in the ICDD database, indicating that it contains 3LiOH·Li 2 SO 4 In addition, Li 3 BO 3 In Examples 1, 2, 4 to 7, 9 to 13, and 15 to 20 in which synthesis was performed, chemical analysis showed that B / S was a value larger than 0, and it was found that the solid electrolyte contained boron.

[0059] It can be seen that the ion conductivity maintenance rate of Examples 3, 8, and 14 without boron is as low as 75% or less. By setting B / S to 0.002 or more as in Example 13, the ion conductivity maintenance rate is increased to 80% or more. In addition, the ion conductivity of Examples 4 and 6 after being kept at 150°C for 100 hours is compared, and it can be seen that the conductivity of Example 4 is lower. It is speculated that this is because: due to Li 3 BO 3 As the amount of boron added is large, the content of the unreacted heterogeneous phase increases, and it can be seen that B / S representing the amount of boron added is preferably less than 1.0.

[0060] Next, in Examples 4 and 6, which were prepared by the melting method with the same composition as Examples 1 and 2, the ion conductivity maintenance rate was relatively high. 2 SO 4 The half-value width of Example 4 and Example 6 is narrower, which indicates that the crystallinity is higher and the crystal is more stable and the conductivity retention rate is increased. 2 SO 4 The half value width is preferably 0.500 or less.

[0061] In addition, the ion conductivity of Examples 6, 11, and 15 detected by XRD after being kept at 150°C for 100 hours is compared. It can be seen that the ion conductivity of Examples 6 and 11 is higher than that of Example 15. If we focus on the peak intensity ratio (I LiOH / I LHS ), and the value in Example 15 is larger, from which it is inferred that LiOH remains as a different phase, and it is inferred that this hinders ion conduction. It is therefore believed that: when LiOH is detected as a different phase, the peak intensity ratio (I LiOH / I LHS ) is preferably 0.234 or less. In addition, Li 2 SO 4 By comparing the ion conductivity of Example 17 and Example 20 after being kept at 150°C, it can be seen that the ion conductivity of Example 17 is higher than that of Example 20. If we focus on the peak intensity ratio (I Li2SO4 / I LHS ), the value of Example 20 is larger, so it is inferred that Li 2 SO 4 It remains as a different phase and is presumed to hinder ion conduction. 2 SO 4 When detected as a different phase, the peak intensity ratio (I Li2SO4 / I LHS ) is preferably less than 1.1.

[0062] In addition, if we focus on Examples 6, 11, 17 and 20, we can know the following. Here, the raw material mixing ratios of these examples are all xLiOH·Li 2 SO 4 ·yLi 3 BO 3 (wherein, 1.0≤x≤4, 0.002≤y≤1), and Li 2 SO 4 :Li 3 BO 3 The ratio is 1:0.05, so it is possible to see the change in characteristics caused by changing only the molar ratio of LiOH (x in the above formula). It was found that in Examples 6, 11, 17 and 20, although the conductivity retention rate after being kept at 150°C for 100 hours all obtained the desired results, the ion conductivity of Examples 6, 11 and 17 with x=3, 2.6 and 2 was higher than the ion conductivity of Example 20 with x=1.0. Therefore, it can be said that from the perspective of ion conductivity, the range of 2.0≤x≤4 and 0.002≤y≤1 is the preferred range.

Claims

1. A solid electrolyte identified as 3LiOH·Li2SO4 by X-ray diffraction, the solid electrolyte also containing boron, and the raw material used to manufacture the solid electrolyte has a composition represented by xLiOH·Li2SO4·yLi3BO3, wherein 1.0≤x≤4, 0.002≤y≤1.

2. The solid electrolyte according to claim 1, wherein A molar ratio of the boron B to sulfur S contained in the solid electrolyte, namely, B / S, exceeds 0.002 and is less than 1.

0.

3. The solid electrolyte according to claim 1 or 2, wherein In the X-ray diffraction pattern of the solid electrolyte using CuKα as a radiation source, the half-value width of the peak near 2θ=18.4° identified as 3LiOH·Li2SO4 is 0.500° or less.

4. The solid electrolyte according to claim 1 or 2, wherein The solid electrolyte was identified as having a peak intensity I near 2θ=20.5° of LiOH in the X-ray diffraction pattern using CuKα as the radiation source. LiOH The peak intensity I near 2θ=18.4° identified as 3LiOH·Li2SO4 LHS The ratio of I LiOH / I LHS Less than 0.

234.

5. The solid electrolyte according to claim 1 or 2, wherein The solid electrolyte was identified as having a peak intensity I near 2θ=22.2° of Li2SO4 in the X-ray diffraction pattern using CuKα as the radiation source. Li2SO4 The peak intensity I near 2θ=18.4° identified as 3LiOH·Li2SO4 LHS The ratio of I Li2SO4 / I LHS Less than 1.

10.

6. The solid electrolyte according to claim 1 or 2, wherein The solid electrolyte is a molten solid.

7. A method for producing a solid electrolyte, which is the method for producing a solid electrolyte according to any one of claims 1 to 6, wherein: include: A process of melting a raw material containing LiOH, Li2SO4 and Li3BO3 and having a composition represented by xLiOH·Li2SO4·yLi3BO3 and cooling it to form a solid, wherein 1.0≤x≤4 and 0.002≤y≤1.

8. A method for producing a solid electrolyte, which is the method for producing a solid electrolyte according to any one of claims 1 to 6, wherein: include: A process for synthesizing a solid electrolyte powder by mixing and pulverizing powders containing LiOH, Li2SO4 and Li3BO3 in a composition ratio represented by xLiOH·Li2SO4·yLi3BO3 using a mechanical ball mill, wherein 1.0≤x≤4, 0.002≤y≤1.